2013
DOI: 10.1038/leu.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα and MYB regulate FLT3 expression in AML

Abstract: The interaction between the receptor FLT3 (FMS-like tyrosine kinase-3) and its ligand FL leads to crucial signalling during the early stages of the commitment of haematopoietic stem cells. Mutation or over-expression of the FLT3 gene, leading to constitutive signalling, enhances the survival and expansion of a variety of leukaemias and is associated with an unfavourable clinical outcome for acute myeloid leukaemia (AML) patients. In this study, we used a murine cellular model for AML and primary leukaemic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…NIPBL-HOXB9, GATA2-HOXA9 , and MN1-FLI1 leukemias all up-regulated Flt3 when compared to normal myeloid progenitors (Supplementary Figure S12C, Table S6). The promoter/enhancer region of Flt3 contains ETS, HOX and GATA binding sites, providing a rationale for the ability of the three different fusion genes to uniformly increase Flt3 expression(43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…NIPBL-HOXB9, GATA2-HOXA9 , and MN1-FLI1 leukemias all up-regulated Flt3 when compared to normal myeloid progenitors (Supplementary Figure S12C, Table S6). The promoter/enhancer region of Flt3 contains ETS, HOX and GATA binding sites, providing a rationale for the ability of the three different fusion genes to uniformly increase Flt3 expression(43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, homeobox transcription factors, such as HOXA9, PBX3 and MEIS1, cooperate to activate FLT3 mRNA transcription and are capable of inducing de novo AMLs when overexpressed [4751]. The bZIP transcription factor CEBPα and the proto-oncogene c-Myb have also been implicated in the FLT3 transcriptional activation in AML [52]. These previous studies clearly demonstrated that aberrant FLT3 activation mediates leukemogenesis triggered by oncogenic transcription factors.…”
Section: Discussionmentioning
confidence: 80%
“…We have demonstrated increases in the expression of not only overall c-Myb but also of c-Myb-9A, an isoform with a "gain -of-function oncogenic characteristics," in ATL cells. In tumors, MYB gene overexpression and its influence on cellular homeo-stasis have been extensively studied (27)(28)(29)(30)(31)(32)(33)(34)(35). Conversely, limited information is available regarding the expression profiles of c-Myb isoforms, each of which possesses a considerably different transactivation capacity and transforming activity.…”
Section: Discussionmentioning
confidence: 99%